Cultures, Worldviews, and Intergenerational Altruism - Kohei Kubota; Akiko Kamesaka; Masao Ogaki; Fumio Ohtake (European Regional Science Association (ERSA), 2013)
This paper presents empirical evidence concerning effects of cultural differences on parents' attitudes toward children from unique U.S. and Japanese survey data. These data sets have been collected by Osaka University, and contain questions concerning worldviews and religions, hypothetical questions about parental behavior, and questions about socioeconomic variables. The data show that U.S. parents tend to be tougher than Japanese parents toward young children. Our evidence suggests that contents of worldview beliefs held by parents affect parents' attitudes toward children. Our empirical evidence also indicates that people who are confident about worldview beliefs tend to show tough attitudes toward their children. Because U.S. parents are much more confident than Japanese parents in worldview beliefs on the average, this cultural difference helps explain a substantial portion of the difference in parental attitudes between U.S. and Japanese parents.
Keywords: 330; Culture; Worldview; Intergenerational Altruism; Temptation; Religion